(untitled) (Journal of the College of Basic Education, 2024)
The research studied presented briefly the most important internal developments in the United States of America during the era of President Millard Fillmore (1850-1853), where these developments had their repercussions on the internal conditions in the United States of America, and the subsequent events that changed the course of domestic politics in the United States of America.